Investigating the validity and reliability of the functional movement screening tool in tennis - Sam Kazemi; Mohammad Hossein Alizadeh; Hassan Daneshmandi (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Recently, researchers use functional movement tests and especially the functional movement screen (FMS) as a screening tool to prevent injuries in sports. However, limited studies are available to strongly support the validity and reliability of the FMS in different sports populations. Therefore, the FMS does not seem to be a comprehensive FMS tool in order to investigate asymmetry and limitations in all sports. Therefore, the aim of the present study was to design and evaluate the validity and reliability of the screening tool for functional movements in tennis. Methods To determine validity and reliability, the results obtained from semi-structured and in-depth interviews with 18 tennis experts were used, which led to the selection of 27 tests out of 108 initial tests. Face validity was evaluated by 10 tennis players, content validity by 10 experts in this field, and construct validity of the questionnaire by 234 tennis players. The reliability of tool was estimated by test-retest method at a time interval of 2 weeks on samples consisting of 20 tennis players using the intraclass correlation coefficient (ICC). Results Based on the results obtained from the calculation of the content validity ratio, 21 out of 27 tests had a content validity ratio higher than 0.62 and the rest of the tests were excluded. Exploratory factor analysis (EFA) extracted two latent factors that explained 54.05% of the total variance. Confirmatory factor analysis (CFA) confirmed the final construct model. The reliability of the tool was estimated: 95% CI: 0.53–0.92, p = 0.001, ICC = 0.91. Conclusion The FMS tool designed for tennis had acceptable validity and reliability with the aim of investigating asymmetry and limitations in this sport. Factor analysis showed that considering the correct features of psychometrics, this tool can be used as a predictor of injury in tennis.